Kearifan Lokal Dalam Pemilihan Umum Kepala Daerah Langsung - Susiatiningsih, Hermini (Faculty of Social and Political Sciences Diponegoro University, 2012)
The theoretical dominance of direct local election is mainly based on western theory ofdemocracy, local politics and development. There are plenty western theories used to analyzecurrent Indonesian local politics, including direct local election. In fact, however, the problemsof local direct election still take place in many forms of disadvantages. These problems are, forinstance, money politics, riots, long conflicts, black campaigns and so forth. In order tominimize these problems, local wisdom based on Javanese values is important in contributionto solve the relevant problems. There are many Javanese value based local wisdom that mayuseful to be implemented.Â